Analysis of Factors Affecting Motor Vehicle Tax Revenue in Bondowoso District - Abdallah Rizal; Diana Dwi Astuti; Haifa (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The main objective of this research is to explain and analyze the factors affecting the revenue from motor vehicle taxes in Bondowoso Regency. This research utilizes a quantitative method. The data source for this study is secondary data obtained from the Bondowoso Central Statistics Agency. The population in this study consists of four variables related to the research. Purposive sampling technique is employed for sample selection, in alignment with the research objectives. Multiple linear regression is used as a hypothesis testing tool with the assistance of SPSS 25 software. The research indicates that the influence of inflation, the number of motor vehicles, the population, and Gross Regional Domestic Product (GRDP) simultaneously affect the revenue from motor vehicle taxes